2017
DOI: 10.1016/j.fertnstert.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Is advanced paternal age a health risk for the offspring?

Abstract: In this article we review the epidemiologic evidence for adverse health effects in offspring of fathers of advanced age. First the evidence regarding fetal survival is addressed, and afterward we review the evidence regarding morbidity in children with older fathers. The adverse conditions most consistently associated with increased paternal age are stillbirths, musculo-skeletal syndromes, cleft palate, acute lymphoblastic leukemia and retinoblastoma, and neurodevelopmental disorders in the autism spectrum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 74 publications
1
68
0
3
Order By: Relevance
“…With the growing understanding of the importance of contributions by men to perinatal health, however, preconception health is increasingly being defined as the health of all people of reproductive age, regardless of sex 13. A key component of preconception health is having a reproductive life plan—defined by the US Centers for Disease Control and Prevention as a plan for “a person’s intentions regarding the number and timing of pregnancies in the context of their personal values and life goals.”14 Given that many couples might not be aware of the potential impact of paternal age on perinatal health, the current findings underscore the importance of including, in reproductive life plans, discussions of paternal age and declines in sperm quality, and other risk factors such as chronic disease, that are related to age 9. Currently, the best method for engaging men in preconception care remains elusive 13.…”
Section: Preconception Healthmentioning
confidence: 88%
See 3 more Smart Citations
“…With the growing understanding of the importance of contributions by men to perinatal health, however, preconception health is increasingly being defined as the health of all people of reproductive age, regardless of sex 13. A key component of preconception health is having a reproductive life plan—defined by the US Centers for Disease Control and Prevention as a plan for “a person’s intentions regarding the number and timing of pregnancies in the context of their personal values and life goals.”14 Given that many couples might not be aware of the potential impact of paternal age on perinatal health, the current findings underscore the importance of including, in reproductive life plans, discussions of paternal age and declines in sperm quality, and other risk factors such as chronic disease, that are related to age 9. Currently, the best method for engaging men in preconception care remains elusive 13.…”
Section: Preconception Healthmentioning
confidence: 88%
“…These factors have also been linked to adverse perinatal outcomes 9. Therefore, although the observed association between paternal age and adverse perinatal outcomes could be real, it might not be causal 9. As described by previous authors, age is both a “biological fact” and a “social construct,”9 and the reasons for delaying childbearing—and their potential influences on perinatal outcomes—should be acknowledged.…”
Section: Three Considerationsmentioning
confidence: 92%
See 2 more Smart Citations
“…Several reports have shown that advanced paternal age is associated with an increased risk of certain cancers and neuropsychiatric diseases in offspring (D'Onofrio et al ., ; Ramasamy et al ., ; Urhoj et al ., ; Frans et al ., ). Nevertheless, the number of expected attributable cases of disease due to older fathers has yet to be determined (Nybo Andersen & Urhoj, ).…”
Section: Introductionmentioning
confidence: 99%